Deposition of Cu/a‐C:H Nanocomposite Films. Issue 9 (1st February 2016) - Hanuš, Jan; Steinhartová, Tereza; Kylián, Ondřej; Kousal, Jaroslav; Malinský, Petr; Choukourov, Andrei; Macková, Anna; Biederman, Hynek
Abstract : In the present study is shown a novel vacuum‐based technique that enables production of hard polymeric nanocomposite coatings with metal (Cu) nanoparticles. This method is based on the use of gas aggregation source (GAS) of Cu nanoparticles and plasma‐enhanced chemical vapour deposition of a‐C:H matrix that was deposited in a mixture of Ar and n‐hexane on the substrates placed on the powered RF electrode. This approach makes it possible to control independently both the properties of the matrix by variation of the applied RF power and the amount of incorporated Cu nanoparticles that may be adjusted by operational parameters of the GAS. Characterisation of the films in terms of their chemical composition, morphology, optical and mechanical properties is described here alongside with description of Cu nanoparticles production using GAS with variable aggregation length. Abstract : Currently, the most often used technology for metal/a‐C:H nanocomposite films deposition is based on the combination of PECVD with simultaneous magnetron sputtering of metal target. This approach suffers from the impossibility to control independently the matrix properties and NPs filling factor and size distribution. It is shown on example of Cu/a‐C:H nanocomposites that this principal drawback may be overcome by a PECVD combined with the deposition of Cu NPs by means of gas aggregation source.